Performa Tutor Sebagai Pendiagnosis Dalam Tutorial Menurut Persepsi Mahasiswa - Wahyuni Utami; Nindya Aryanty (JAMBI MEDICAL JOURNAL "Jurnal Kedokteran dan Kesehatan", 2013)
ABSTRACT Background: Tutors are needed to facilitate tutorial  in order to ensure student achieving learning objective. In tutorial, tutor has a role as diagnostician that is tutor need to diagnose student prior knowledge. Tutors performance as diagnostician in medical faculty of Jambi University never have been studied. Objectives: This study aim to analyse tutors performance as diagnostician on tutorial in medical faculty of Jambi University based on students perception. Methods: This descriptive study involved 108 students of Block 17 (Reproductive System Block)  and 98 students of Block 11 (Urogenital System and Body Fluid Block) who are devided into 20 different tutorial groups. Tutor performance is assessed using questioners constructed based on theory (α cronbach 0,9093). Results: Data of 22 tutors performance were collected. Students perceived 2 tutors performed very good as a diagnostician. Another 19 tutors (86,4%) performance were rated as good, and 1 tutors (4,5%) were rated as fair. Data also showed that tutors performed poor on conducting several activities, such as come on time and stimulate students to discuss the next question if the student’s response to the questions declining. Conclusion: Students perceived numbers of tutor in medical faculty of Jambi University performed well as a diagnostician. However, Institutions still need to improve tutors performance by training and comprehensive evaluation Keyword: Diagnostician, Performance, Tutor.